AN ANALYTICAL STUDY OF POTATO SEED PRODUCTION IN JALANDHAR DISTRICT OF PUNJAB - Sandhu, Lavleen Kaur (Potato Journal, 2022)
Seed is an essential input for the potato crop. Much of the efforts and investment would be infructuousif the farmers did not get the quality seeds. Only the seed with assured purity-genetic and physical can be expected torespond to fertilizers and other inputs in a respected manner. The present study attempted to analyze the source, SRRof potato seed and assess the effect on potato crop yield by using certified seed in the Jalandhar district of Punjab. Thecurrent study was conducted on primary data collected from 120 farmers during the 2020-21 agricultural year. The datawere analyzed using simple tabular analysis and other suitable statistical techniques. The study found that the mostpreferred source of seed was the self-retained seed which came out to be 48 per cent, the second most preferred sourcewas private seed dealers, as 17 per cent procured seed from these dealers. The high use of self-retained seed was due tothe high cost of purchased seed, and the other reason was that farmers had more confidence in the self-retained seed.The study found that large farmers’ Seed Replacement Rate (SRR) was higher. It was 11.2 per cent for small farmers, 19.5per cent for medium farmers and 27.5 per cent for large farmers. The yield of potato crop using certified seed was higherthan non-certified seed. The per cent difference in yield of potato grown by certified and non-certified seed among smalland medium farmers was 17 per cent, 11 per cent among large farmers and 15 per cent overall in the Jalandhar district ofPunjab. The study highlighted that the primary constraint faced by potato seed growers were high prices of certified seed(69.1 per cent), high cost of pesticides and insecticides (65.8 per cent), fluctuations in the price of potato seed (55 per cent),lack of public procurement at MSP (53.3 per cent), covid related restrictions (52.5 per cent) and lack of extension facilities(48.3 per cent). The study suggested that the government should provide certified seed to the farmers at the lowest costto increase the seed replacement rate. Awareness regarding the use of certified seed should be given to farmers throughextension services. Government institutes like Central Potato Research Station (CPRS) (ICAR), the Centre of Excellence(Dogri) and the Department of Horticulture should expand the production of certified seeds as only 18 per cent of potatogrowers purchased seeds from these agencies in the study area. The minimum support price of potatoes should be fixedto promote the production of potatoes in the state.